(untitled) (Applied Biological Research, 2016)
Botryotinia ricini (Godfrey) Whetzel, the gray mold pathogen of castor, inflictsserious crop lossesin short periods. The presentstudywasaimedat to develop a season-independent screening technique for gray mold in castor. Conidia from in vitro-raised pure culture of the anamorph Amphobotrys ricini were sprayed on separated mature as well as immature capsules of 4 castor genotypes (DCS 9, RG 2787, RG 3309 and RG 3216 R), placed in glass petriplates and incubated at 22-24ºC for 7 days. Genotype DCS-9 was highly susceptible to the disease, while genotype RG 3216 R exhibited least susceptibility. Immature capsules were more susceptible to disease than mature capsules. RNA degradation occurred in treated samples 2 days after treatment and control gene (UBQ) expression was unaffected till 4 hr post inoculation. Thus a reproducible, lab-based, season-independent, screening technique using petri-plates and severed castor capsules was developed for differential gene expression analysis of candidate genes involved in early infection and elucidating host-pathogen interactions in castor gray mold.